2016
DOI: 10.1007/s10668-016-9782-y
|View full text |Cite
|
Sign up to set email alerts
|

Solid waste management in Bogotá: the role of recycling associations as investigated through SWOT analysis

Abstract: Migration to urban centres is among the most important forces in contemporary urban studies. In this paper, we study how the demography and epidemic profile of a community are altered when they transition from living in nomadic conditions in a forested environment to a peri-urban settlement in a city of the Amazon basin. We analyse demographic and epidemic data with a multilevel model to understand individual and community-level effects in terms of the risk of malarial infection. We show that malaria becomes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
0
24
0
3
Order By: Relevance
“…Appropriate strategies should be introduced for supporting these activities, such as improved public awareness, enaction of specific laws and regulations and implementation of SWM infrastructures. For instance, a study conducted in Bogotá (Colombia), found that the main external requirements for including the activity of the informal sector regards the recognition of recyclers’ work, the formal alliances with the productive sector and the stabilization of the prices of recycling material [146]. Therefore, actions should be implemented both by private companies and local governments.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate strategies should be introduced for supporting these activities, such as improved public awareness, enaction of specific laws and regulations and implementation of SWM infrastructures. For instance, a study conducted in Bogotá (Colombia), found that the main external requirements for including the activity of the informal sector regards the recognition of recyclers’ work, the formal alliances with the productive sector and the stabilization of the prices of recycling material [146]. Therefore, actions should be implemented both by private companies and local governments.…”
Section: Discussionmentioning
confidence: 99%
“…On average, each municipality has 2 or 3 compactor vehicles with sufficient capacity to carry out the collection. This type of vehicles allows a greater load capacity and a better control of leachate and offensive odors generated by solid waste [65].…”
Section: Discussionmentioning
confidence: 99%
“…The SWOT analysis has been extensively used in the literature for the analysis and effectiveness of a business or plan. In the waste management sector, SWOT analysis has been used to identify S trengths, W eaknesses, O pportunities and T hreats in various municipalities around the world (Pardo Martínez and Piña, 2017; Shahba et al, 2017; Yuan, 2013) either to discover the potentials and ways for initiating and successfully implementing an effective SWM programme, or to prove the importance of implementing a viable and sustainable waste management sector, in order to resolve environmental concerns, regarding the pollution and protection of natural resources.…”
Section: Swot Analysis On Candd Waste Practices In the State Of Qatarmentioning
confidence: 99%